(untitled) (CIPEEX, 2025)
Police Power is a type of administrative power, legally provided in Article 78 of Law No. 5,172/1966, consisting of the Public Administration’s authority to restrict and condition the exercise of rights and private activities to protect collective interests. It can be understood broadly, encompassing all state actions that limit individual freedom for the benefit of society, or narrowly, referring to administrative activities granting agents the prerogative to limit freedom and property. Two types are identified: administrative police, focused on individual activities and preventive in nature; and judicial police, directed at individuals responsible for offenses and mainly repressive. Police Power may be exercised directly by government entities (Direct Administration) or delegated to public or private legal entities. It unfolds in four stages: legislation, consent, supervision, and sanction. Its main attributes are discretion, self-executing authority, and coercibility.